Literature Article Review: Gambir Plant (Uncaria gambir Roxb) as Antioxidant Producer - Rahmawati, Atika Ayu; Yuniarti, Elsa (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Abstract Gambier (Uncaria gambir Robx) is one of the typical spices of West Sumatra which contains chemical compounds and bioactive components that have the potential to be used as raw materials for medicines in the pharmaceutical industry. The bioactivity of this gambier plant can stimulate and enhance the immune system. The purpose of study is to present a summary of the literature review to gather overall information about the gambier plant as an antioxidant producer. The method used in literature review article research is the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) approach. Using literature in the form of Publish or Perrish, (2010-2023). Based on the results of the literature review, 12 journals were obtained. Based on the results of a literature review article showing various properties found in gambier plants due to suspected chemical compounds including phenolics and flavonoids such as quercetin and catechin, which have potential bioactivity, namely having antioxidant and anti-inflammatory properties. From several research results, the gambier plant part is proven to have many pharmacological properties that can increase the productivity of drugs with natural ingredients. Key words : Gambir, Antioxidant, Bioactive Compound, Literature Review